(untitled) (Scientific journal of the Fergana State University, 2024)
In order to study the distribution, morphology and bioecology of members of the Curculionidae family in the Fergana Valley, a study was conducted in March-May. As a result of the conducted research, Lichus Bardanae J.C. was found in the Fergana Valley. Fabricius was determined and its morphology and bioecology were studied. This study was conducted in the foothills and hills of Andijan, Fergana, and Namangan regions of the Fergana Valley. In this article, Lichus Bardanae J.C. in Fergana Valley. Fabricius, studies on distribution, systematics and morphology and bioecology are highlighted.